PENGARUH PENAMBAHAN CACAHAN LIMBAH PLASTIK JENIS HIGH DENSITY POLYETHYLENE (HDPE) PADA - Sina, Dantje A. T.; Udiana, I Made; Da Costa, Bernad D. (Jurnal Teknik Sipil, 2012)
Waste is a very complex problem in urban area. Plastic waste is increasing every year. Kupang with population of 291,794 people generate waste reaches 926 m3/day. Organic waste to 700 m3 and inorganic waste about 226 m3. Concrete is planned by strength quality 25 MPa. Based on the analysis in this study obtained that concrete flexural strength value increased due to the addition of HDPE plastic shredded into the concrete, with chopped levels are added to the concrete at 0%, 0.50% and 0.90% .0,70%. Flexural strength value of normal concrete without the addition of shredded plastic (0%) is 4.12 MPa, flexural strength of concrete with the addition of shredded plastic 0.50% is 4.30 MPa increased 4.37% from normal concrete flexural strength, flexural strength of concrete with the addition of shredded plastics 0.70% is 4.21 MPa increased 2.19% from the normal concrete flexural strength and flexural strength of concrete with the addition of shredded plastic 0.90% is 3.94 MPa decreased 3.64% of flexural strength normal concrete.